Reflective Approach to Self-Assessment of Professional Educational Activity by University Professors - Tatyana P. Gordienko, Lyenuza Z. Tarkhan, Mariia I. Mykhniuk, (Opción, 2019)
The research objective was to analyze the requirements for the professional ethical conduct of accountants. The data analysis stage comprised deduction, induction, and smart modeling that allowed making a connection with psychological knowledge and to critically reconsider the basic concepts of professional ethics of accountants and auditors. As a result, a large majority of the colleagues (96.9%) organizes and maintains accounting records by focusing on the needs and interests of the top management. In conclusion, by honesty, the Code means the accountant’s responsibility to act in an open and honest manner in all professional and business relationship